Evaluation and integration of ICT using music software in music education - Jia Li (Pejabat Karang Mengarang UPSI, 2022)
The primary goal of this research was to assist music education instructors in the integration of ICT into their classrooms and utilized music software. It also sought to get a better knowledge of how instructors made use of ICT, as well as to identify and evaluate their training requirements, as well as to assess the extent to which ICT was utilized in instructional programs. The researchers also looked at the obstacles that instructors encountered when integrating ICT into music education courses, as well as their perceptions of the technology's usefulness. This study utilized qualitative method and used written documents as where the researcher got the data. According to the findings of the study, technology helps to make the learning environment more alive and appealing. It will demonstrate how interactive music educational techniques and ICT tools were used in schools to teach music education and how they encourage the teaching of music education. It will also demonstrate how interactive music educational methods and ICT tools were used in schools to teach arithmetic.